EFEKTIVITAS PELAYANAN DALAM PEMBUATAN AKTA KELAHIRAN DI KECAMATAN BUKIT BATU KABUPATEN BENGKALIS - Adli Ahmad; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Service is one of the things that really need to get the attention of the government, so that the user community services were satisfied with the service provided. In relation to the above Department of Population and Civil Registration Bukit Batu District is one of the agencies authorized to provide services to the community, which of especially in the areas of service. Birth certificate is a certificate issued by the competent authority, which is related to the birth in order to acquire or obtain legal certainty against someone. Deed made based on reports of births conveyed within the time limit no later than 60 (sixty) working days for the citizen and 10 (ten) working days from the date of birth for foreigners baby. The research to aims identify and analyze of Birth Certificate Child Care Arrangements in the District Of Bukit Batu. The writer used qualitative method and the technique of collecting data are interview, observation and documentation. The interview was conducted by the research informants defined through snowball sampling technique.The theory of Bronoos in Sutupo will be used as reference to analyze and ędefines the overall area is service a birth certificate there are some good service quality criteria which professionalism and skills, attitudes and behaviors, and trustworthy reliability, accessibility and flexibility, improved. Data collection using the techniques of observation and interviews. Data analysis techniques using qualitative descriptive techniques.The result of showed, Effectiveness a obtaining of certificate service has not running well based on the minimum service’s standart that have been established in regulations. This matter could be seen from the phenomenon and fact of the implementation of certificate service that occured on the real life. The factors that influenced the implementation of Department of Population and Civil Registration Pekanbaru City regency are : Human resources, infrastructure and leadership.Key words: Care, Birth Certificate, Department of Population and Civil Registration